Association between weight-adjusted-waist index and serum anti-aging protein α-Klotho in U.S. adults: Evidence from NHANES 2007–2016 - Zujun Wen; Xiang Liu; Tingting Zhang; Junhai Zhang; Zhicong Zou; Shuncheng Jiang; Shusi Li (Experimental Gerontology)
Background: As unhealthy diets have proliferated, there has been an increasing trend in the prevalence of obesity along with socioeconomic progress. WWI, mainly representing weight-independent central obesity, is a more accurate indicator of obesity than BMI and WC. Klotho is known to be one of the root causes of several age-related illnesses. There has never been any prior evidence associating WWI and serum α-Klotho levels. Methods: The current cross-sectional investigation used data from the National Health and Nutrition Examination Survey (NHANES) 2013–2016. The calculation of each participant's WWI involved dividing their waist circumference in centimeters by the square root of their weight in kilograms. Using multivariable linear regression models, the association between serum Klotho concentrations and WWI was analyzed. Smoothed curve fitting was utilized to investigate the nonlinear connection. In addition, interaction tests and other subgroup analyses were carried out. Results: With an average age of 57.57 ± 10.81 years, 13,172 participants were enrolled in this study, of whom 51.45 % were female. After full adjustment, each unit increase in WWI was significantly associated with a decrease in Klotho by 23.18 ng/ml [β(95%CI) = −23.18 (−31.34, −15.02)]. Moreover, we uncovered that WWI had a stronger negative correlation with Klotho than other obesity markers, such as WC, body mass index (BMI), and a body shape index (ABSI). Conclusions: To sum up, weight-adjusted-waist index levels were negatively associated with serum Klotho protein concentration and showed a stronger correlation than other obesity markers. Our findings indicated that WWI may be a predictor of reduced Klotho levels, and that controlling obesity in accordance with WWI may help lower the Klotho levels.